Density and selected mechanical properties of stemwood and branchwood of Brachystegia spiciformis and Julbernadia globiflora - Khan, Inayat; Bila, Narciso; Manhica, Alberto; Uetimane, Ernesto Jr.; Egas, Andrade; Möttönen, Veikko (Natural Resources Institute Finland, Luke, 2017)
The highly selective nature of the logging operations is rapidly decreasing the value of most forested areas in Mozambique due to lack of knowledge on properties of the overlooked species. In this study, a comparative assessment between branchwood and stemwood density along with some mechanical properties of two very abundant species (Brachystegia spiciformis and Julbernadia globiflora) was carried out in order to explore potential uses of branchwood. For each species, a total of five undated heavily branched trees were harvested in their natural habitats. Afterwards, samples from the main stem (bottom and top) and branches were separately prepared based on ISO standards for testing density and mechanical tests at 12% moisture content such as static bending (MOE and MOR) and compression (parallel and perpendicular to axial fibres) properties. The results show that in general branchwood is denser compared to the wood of main stem. However, the pairwise comparison across the wood sections did not produce significant differences, suggesting uniformity, especially in terms of density. The same trend was also observed for the mechanical properties, with the exception of branchwood MOE of Julbernadia globiflora to which significant difference was reported against either stemwood section. The global assessment of the results suggests a safe and interchangeable use of branchwood to supplement raw material for purposes commonly known for the stemwood. Therefore, the use of heavily branched trees is expected to increase sawing yield as well as halting deforestation rate.
Keywords: wood strength; wood properties; wood density